PJMHS 2022
DOI: 10.53350/pjmhs20221612403
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hematological Malignancies Based on Bone-Marrow Aspiration and Trephine Biopsy in Patients Presenting to Tertiary Care Hospital

Abstract: Background: Hematological disorders are found commonly in the general population existing on both ends of the spectrum with minute disorders like iron deficiency anemia to as severe as bone marrow infiltration Objective: To assess the frequency of hematological malignancies based on bone-marrow aspiration and trephine biopsy in patients presenting to tertiary care hospital Methodology: The current study was cross-section descriptive study carried out at the Pathology department of Bacha Khan Medical College, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The diagnosis of acute leukemias on bone marrow biopsy in our study was supplemented by Flow Cytometry either on peripheral blood sample or bone marrow aspirate sample. In contrast to our findings, a study by Iqbal et al reported a different distribution, with acute myelogenous leukemia diagnosed in 23.08% of patients and acute lymphoblastic leukemia in 23.08% [12]. This difference could be attributed to variations in age distribution, with ALL being more prevalent in children and AML in adults.…”
Section: Discussioncontrasting
confidence: 99%
“…The diagnosis of acute leukemias on bone marrow biopsy in our study was supplemented by Flow Cytometry either on peripheral blood sample or bone marrow aspirate sample. In contrast to our findings, a study by Iqbal et al reported a different distribution, with acute myelogenous leukemia diagnosed in 23.08% of patients and acute lymphoblastic leukemia in 23.08% [12]. This difference could be attributed to variations in age distribution, with ALL being more prevalent in children and AML in adults.…”
Section: Discussioncontrasting
confidence: 99%